Automated liquid handling systems for microfluidic applications - Idinyang, Solomon (2017)
Advances in microfluidic research have improved the quality of assays performed in micro-scale environments. Improvement of liquid handling techniques has enabled efficient reagent and drug use while minimising waste. The requirements for the applied techniques vary with applications and a custom integrated liquid handling solution was developed to accomplish some of these applications with minimal changes to the system. It is desirable to employ this technology to neuroscience research that requires a fluidic system that can test theories of reinforcement learning in neuronal cultures. An integrated system is therefore required to implement transport and manipulation of media and drugs loaded in a microfluidic device. One requirement for such an integrated system for liquid handling is a transport mechanism to deliver reagents and nutrients to cultures. A liquid flow control system is required to allow precise and timely control of flow rates through a microfluidic device. This can be extended to enable more sophisticated drug delivery approaches like gradient generation, spatial drug distribution and high temporal resolution of the drugs delivered. Another requirement for an integrated system is a liquid loading system that is capable of inserting specified drugs into the flow line. Such a loading system would allow any number of drugs to be loaded during an experimental process to the microfluidic device containing cells as part of an assay. The integration of these systems will allow researchers take advantage of the combined systems. Software development process should also be undertaken to improve the modularity of the integrated system so that hardware changes have marginal effects on the system operation. The project scope was the development of these liquid handling systems as well as their integration in hardware and software to enable their spatio-temporal drug delivery to neuronal cultures in microfluidic devices. The approach was to optimise performance of custom liquid handling system which was developed to realise fast flow rate changes within 1 second interval. Macro- and micro-scale solutions have been investigated in order to realise effective off-chip liquid loading capabilities. Emphasis has been placed on ease of use, modularity, rapid prototyping and precision. A commercial autoloader was identified as a starting point for sequential drug delivery. This was characterised for suitability and the constraints with this setup was used to identify additional requirements for the development of a novel sequential liquid injection system. The design process of the novel liquid injection system was unable to realise a working system due to mechanical and operational challenges encountered. A modular on-chip liquid manipulation system has been investigated and proposed to realise the sequential injection requirements. Rapid prototyping techniques that can promote ubiquitous microfluidic applications have been identified and verified. An integrated liquid manipulation system has been developed using the commercial autosampler that enables sequential loading of agonists into the microfluidic device as well as reliable chemical signalling of the loaded drugs by switching flow rates of the inputs to the device. This system will be beneficial towards research of other cell types within other research fields requiring similar functionality.